Istifadhah Witness (Testimonium De Auditu) for Marriage Authentication (Analysis of Kuala Simpang Religious Court Ruling Number: 10/Pdt.P/2021/MS.Ksg) - Mubarrak, Husni; Ali, Bukhari; Rahmadani, Sindi (Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This article would like to discuss about istbat nikah (marriage authentication) where the witnesses who gave their testimonies were istifadhah witnesses (Testimonium De Auditu) based on a case which registered in Mahkamah Syar’iyah (Religious Court) in Kuala Simpang, Aceh, as a case number 10/Pdt.P/2021/MS.Ksg. However, based on this witness’ testimonies, the judges authorized istifadhah witnesses to give their testimonies to be heard in front of the Court. It has challenged academically to know and dig more about the judge’s reasoning on why he consider the authorization of istifadhah witnesses testimonies in istbat nikah on mentioned case. It is also interesting to analyze on how Islamic law view about istifadhah witnesses’ testimonies in an istbat nikah case. The combination between field study and library study with juridical normative approach is used as the method in this research. The result shows that istifadhah witnesses’s testimonies can be heard in the court as long as the testimonies given cannot be proved, otherwise then the testimonies are true. Similarly, Islamic law views this matter can only be applied in some cases, one of which is in istbat nikah case.